Amanzi Ayatsha : exploring the integration of environmental sustainability in strategic planning in a public water utility in South Africa - Besharati, Neissan (University of Pretoria, 2025)
Mini Dissertation (MPhil (Corporate Strategy))--University of Pretoria, 2024.